(untitled) (Research, Society and Development, 2022)
The stimulus to reading and scientific knowledge can be worked together in learning processes through scientific dissemination. This type of approach enables a better understanding of how the concepts and phenomena of nature arise using the History of Science in the classroom. The present work aims at the dissemination and appropriation of the history of the invention of the photophone, in the teaching of physics, using extracts from a historical article about it and the use of the production of a comic book, applying a workshop on the use of this graphic technique. The study was developed with four classes at Kennedy High School, in February and March 2021, via remote system, being 2 classes from the 9th year of elementary school and 2 classes from the 1st year of high school. After the workshop, the students built comics about the history and functioning of the photophone. The analysis of the comics, as well as the results of the applied questionnaire, enabled to know the degree of reading comprehension the students acquired mediated by the graphic and written languages they produced. Therefore, it was possible to highlight that the use of the theme, in classroom, involving History of Science and the use of the comic book construction tool had a motivating effect on the students and allowed them to verify their appropriation of important aspects of the scientific understanding of the issue at stake.